Circle inscribed in two intersecting parabolas

Geometry Level 4

The circle centered at the origin ( 0 , 0 ) (0,0) is inscribed in the two curves

x 2 + 2 x y + y 2 2 x + 2 y = 8 x^2 + 2xy + y^2 - \sqrt{2}x + \sqrt{2}y = 8 and x 2 + 2 x y + y 2 + 2 x 2 y = 8 x^2 + 2xy + y^2 + \sqrt{2}x - \sqrt{2}y = 8

Let A T A_{T} be area of R 1 + R 2 R_{1} + R_{2} , where R 1 R_{1} is the region between x 2 + 2 x y + y 2 2 x + 2 y = 8 x^2 + 2xy + y^2 - \sqrt{2}x + \sqrt{2}y = 8 and the inscribed circle and R 2 R_{2} is the region between x 2 + 2 x y + y 2 + 2 x 2 y = 8 x^2 + 2xy + y^2 + \sqrt{2}x - \sqrt{2}y = 8 and the inscribed circle.

If A T = a b c d b e d arcsin ( c d b e ) A_{T} = \dfrac{a}{b}\sqrt{\dfrac{c}{d}} - \dfrac{be}{d}\arcsin\left (\sqrt{\dfrac{cd}{be}}\right ) , where a , b , c , d a,b,c,d and e e are coprime positive integers,

find a + b + c + d + e a + b + c + d + e .


The answer is 48.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Mar 28, 2021

( 1 ) : x 2 + 2 x y + y 2 2 x + 2 y = 8 (1): \:\ x^2 + 2xy + y^2 - \sqrt{2}x + \sqrt{2}y = 8

( 2 ) : x 2 + 2 x y + y 2 + 2 x 2 y = 8 (2): \:\ x^2 + 2xy + y^2 + \sqrt{2}x - \sqrt{2}y = 8 .

The equations of rotation are:

x = x cos ( θ ) y sin ( θ ) x = x'\cos(\theta) - y'\sin(\theta) and y = x sin ( θ ) + y cos ( θ ) y = x'\sin(\theta) + y'\cos(\theta) .

Since C o e f f ( x 2 ) = C o e f f ( y 2 ) Coeff(x^2) = Coeff(y^2) in both curves θ = 4 5 \implies \theta = 45^{\circ} \implies

x = x y 2 x = \dfrac{x' - y'}{\sqrt{2}} and y = x + y 2 y = \dfrac{x' + y'}{\sqrt{2}}

( 1 ) x 2 2 x y + y 2 2 + ( x 2 y 2 ) + x 2 + 2 x y + y 2 2 ( x y ) + x + y = 8 (1) \implies \dfrac{x'^2 - 2x'y' + y'^2}{2} + (x'^2 - y'^2) + \dfrac{x'^2 + 2x'y' + y'^2}{2} - (x' - y') + x' + y' = 8

x 2 + y = 4 y = 4 x 2 \implies x'^2 + y' = 4 \implies \boxed{y' = 4 - x'^2} and similarly for ( 2 ) (2) we have: y = x 2 4 \boxed{y' = x'^2 - 4} .

Using y = 4 x 2 D = d 2 = x 2 + ( 4 x 2 ) 2 = x 4 7 x 2 + 16 y' = 4 - x'^2 \implies D = d^2 = x'^2 + (4 - x'^2)^2 = x'^4 - 7x'^2 + 16 \implies

d D d x = 2 x ( 2 x 2 7 ) = 0 \dfrac{dD}{dx'} = 2x'(2x'^2 - 7) = 0 and x 0 x = ± 7 2 y = 1 2 x' \neq 0 \implies x' = \pm\sqrt{\dfrac{7}{2}} \implies y' = \dfrac{1}{2} \implies

D = d 2 = 15 4 D = d^2 = \dfrac{15}{4}

and d 2 D d x 2 > 0 \dfrac{d^2D}{dx'^2} > 0 \implies the distance d d is minimized when x = ± 7 2 x' = \pm\sqrt{\dfrac{7}{2}}

For R 1 : R_{1}:

x 2 + y 2 = 15 4 y = 15 4 x 2 x'^2 + y'^2 = \dfrac{15}{4} \implies y' = \sqrt{\dfrac{15}{4} - x'^2} and y = 4 x 2 y' = 4 - x'^2 \implies

A = 7 2 7 2 4 x 2 15 4 x 2 d x A = \displaystyle\int_{-\sqrt{\frac{7}{2}}}^{\sqrt{\frac{7}{2}}} 4 - x'^2 -\sqrt{\dfrac{15}{4} - x'^2} dx'

Let x = 15 2 sin ( θ ) d x = 15 2 cos ( θ ) d θ x' = \dfrac{\sqrt{15}}{2}\sin(\theta) \implies dx' = \dfrac{\sqrt{15}}{2}\cos(\theta) d\theta \implies

15 4 x 2 d x = 15 8 1 + cos ( 2 θ ) d θ = 15 8 ( θ + sin ( θ ) cos ( θ ) ) \displaystyle\int \sqrt{\dfrac{15}{4} - x'^2} dx' = \dfrac{15}{8}\displaystyle\int 1 + \cos(2\theta) d\theta = \dfrac{15}{8}(\theta + \sin(\theta)\cos(\theta)) \implies

7 2 7 2 15 4 x 2 d x = \displaystyle\int_{-\sqrt{\frac{7}{2}}}^{\sqrt{\frac{7}{2}}} \sqrt{\dfrac{15}{4} - x'^2} dx' = 15 8 ( arcsin ( 2 x 15 ) + 2 x 15 4 x 2 15 ) 7 2 7 2 \dfrac{15}{8}(\arcsin(\dfrac{2x'}{\sqrt{15}}) + \dfrac{2x'\sqrt{15 - 4x'^2}}{15})|_{-\sqrt{\frac{7}{2}}}^{\sqrt{\frac{7}{2}}}

= 15 4 arcsin ( 14 15 ) + 14 4 = \dfrac{15}{4}\arcsin(\sqrt{\dfrac{14}{15}}) + \dfrac{\sqrt{14}}{4} \implies A = 31 6 7 2 15 4 arcsin ( 14 15 ) A = \dfrac{31}{6}\sqrt{\dfrac{7}{2}} - \dfrac{15}{4}\arcsin(\sqrt{\dfrac{14}{15}})

Using symmetry A T = 2 A = 31 3 7 2 15 2 arcsin ( 14 15 ) = \implies A_{T} = 2A = \dfrac{31}{3}\sqrt{\dfrac{7}{2}} - \dfrac{15}{2}\arcsin(\sqrt{\dfrac{14}{15}}) =

a b c d b e d arcsin ( c d b e ) a + b + c + d + e = 48 \dfrac{a}{b}\sqrt{\dfrac{c}{d}} - \dfrac{be}{d}\arcsin(\sqrt{\dfrac{cd}{be}}) \implies a + b + c + d + e = \boxed{48} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...